Dual checkpoint inhibitor induced autoimmune encephalitis - Elkayam, Natalie (Archive of Oncology, 2019)
Immune checkpoint inhibitor therapy has become increasingly more used as a treatment modality for solid organ tumors. Nivolumab, anti-PD-1 and Ipilimumab, anti-CTLA-4 monoclonal antibodies are checkpoint inhibitors with well described immune related toxicities. Immune specific neurotoxicity is rare and not well elucidated in literature. We present a case of severe autoimmune encephalitis in a patient with metastatic renal cell carcinoma treated with both Nivolumab and Ipilimumab. A 53-year-old man with metastatic renal cell carcinoma presented due to visual and auditory hallucinations of sudden onset, confusion and weakness. Initial imaging and diagnostic workup did not demonstrate a clear source. However, a neurological etiology was suspected. It was concluded that the patient had autoimmune encephalitis induced by dual check point inhibitor therapy. This was further strengthened by his rapid response to systemic corticosteroid therapy. We present a summary of this case and its management and a review of literature on dual checkpoint inhibitor induced neurological adverse effects.